Hermeneutika Hadis Sa’dudin Al-Utsmani: Studi Kitab Al-Manhaj Al-Wasthi Fi At-Ta’amil Ma'a Al-Sunnah Al-Nabawiyyah - Mutia Mahdalena Efendi; Wely Dozan (Sophist : Jurnal Sosial Politik Kajian Islam dan Tafsir, 2020)
The term heremeneutics in contemporary thought is often used as a reference in understanding the text of the Qur'an and Hadith. Hermeneutics serves as a tool for producing understanding and the most well-known methodology for understanding texts contextually and structurally well. The focus of this research will be to map understanding significantly through the hermeneutic theory of contemporary ulama, namely Sa'dudin al-Ustmani in his book "Manhaj Sunnah An-Nabawiyyah". This paper aims to explore methodologi understanding through hermeneutic theory of hadith which produces three important aspects in understanding the Sunnah of An-Nabawiyyah, namely: First, Tasarruf in religious matters conveyed by the apostle. Second, the tasarruf in the religion that is ijtihadi by the Prophet is the error of revelation and sometimes it is wrong but it does not continue in the error, usually there is revelation that justifies it. The revelation that justifies this is sometimes in the form of al-Qur'an, sometimes it is also not the third al-Qur'an, tasarrufat in world affairs. The basic assumption of the author is to describe and describe the contemporary scholar Sa'dudin Al-Ustmani in his book Manhaj sunah an-nabawiyah whose book aims to provide an intermediate understanding in understanding the sunnah an-nabawiyah.